CORRELATION OF NUTRITIONAL STATUS AND DIETARY HABIT WITH THE INCIDENCE OF ANEMIA IN ADOLESCENT GIRLS - Anik Sulistiyanti; Nessatania Selfiani Widodo; Dian Nirmala Sari (LPPM Universitas Duta Bangsa Surakarta, 2022)
Adolescence is a period where growth occurs rapidly, so that the nutritional needs of adolescence also increase. One of the nutrients whose needs are increasing is iron. The purpose of this study was to determine the relationship between nutritional status and diet with the incidence of anemia in adolescent girls. The method used in this research is an analytic observational research with a cross sectional research design. The research population is all young women at SMK Citra Medika Sragen. The research sample was 160 adolescent girls using stratified random sampling technique. Data analysis using univariate analysis and bivariate analysis using chi square test with 95% confidence level. The results of the study using statistical tests with chi-square values ​​obtained on nutritional status with the incidence of anemia were p value = 0.008 <0.05. The results of the analysis of eating patterns with the incidence of anemia are p value = 0.004 < 0.05 with an OR of 0.409. The conclusion of this study is that there is a correlation between nutritional status and dietary habit with the incidence of anemia in adolescent girls